2010
DOI: 10.1074/mcp.m900540-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

Post-translational Modifications Differentially Affect IgG1 Conformation and Receptor Binding

Abstract: Post-translational modifications (PTMs) can have profound effects on protein structure and protein dynamics and thereby can influence protein function. To understand and connect PTM-induced functional differences with any resulting conformational changes, the conformational changes must be detected and localized to specific parts of the protein. We illustrate these principles here with a study of the functional and conformational changes that accompany modifications to a monoclonal immunoglobulin ␥1 (IgG1) ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
339
3
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 370 publications
(376 citation statements)
references
References 52 publications
33
339
3
1
Order By: Relevance
“…No difference in binding was observed after oxidative stress (Table 3), which is generally found in the literature as well 14, 20. Only Bertolotti‐Ciarlet et al .…”
Section: Resultssupporting
confidence: 73%
“…No difference in binding was observed after oxidative stress (Table 3), which is generally found in the literature as well 14, 20. Only Bertolotti‐Ciarlet et al .…”
Section: Resultssupporting
confidence: 73%
“…Although it is known that amino acid oxidation can occur during sample preparation, it is tempting to speculate that the oxidative modification of certain circulating IgGs may have resulted from in vivo posttranslational modifications rather than processing artifacts, because plasma cells experience high levels of oxidative stress (34), and the t 1/2 of circulating Igs in serum is >1 wk, resulting in extensive exposure of antibodies to oxidizing conditions. L-Methionine oxidation has also been observed repeatedly in recombinantly expressed therapeutic antibodies from CHO cells (35,36). Additional studies will be needed to determine the extent of L-Methionine oxidation during sample processing and the frequency of in vivo modification.…”
Section: Discussionmentioning
confidence: 99%
“…, 67-69 By carrying out enzymatic hyper-galactosylation across four batches of monoclonal antibodies produced from standard manufacturing processes in CHO cells, Thomann et al. demonstrated that hyper-galactosylation of antibody samples consistently leads to improvement in FcγRIIIa binding and ADCC 68 .…”
Section: Fc Galactosylation and Sialylation Also Modulate Igg1 Interamentioning
confidence: 99%